Genistein Precipitated Hypothyroidism, Altered Leptin and C-Reactive Protein Synthesis in Pregnant Rats (Nigerian Journal of Physiological Sciences, 2021)
Summary: Genistein is an isoflavone constituent of soya. This study examined the mechanism by which genistein produced adverse effects in pregnant laboratory rats. Pregnant rats were divided into control (Con) and genistein (Gen) force fed (2 mg/kg) groups. At terminal gestation day (GD) ranging from 0-20, the rats were sacrificed, and blood samples and amniotic fluids were collected. Thyroid hormone, C-reactive protein (CRP) and leptin assay was carried using the blood samples. Leptin was also assayed in the placenta and amniotic fluid supernatant. Oral exposure of pregnant rats to genistein significantly altered maternal T3, (GD18; Con 1.65 ± 0.01, Gen 1.03 ± 0.04 nmol/L), T4 (GD6; Con 29.60 ± 0.00, Gen 36.04 ± 1.29 nmol/L), Leptin (Placenta GD20; Con 0.08 ± 0.01, Gen 0.31 ± 0.02 ng/ml, amniotic fluid ;GD 20; Con 0.02 ± 0.00, Gen 0.35 ± 0.05 ng/ml) in genistein group. These changes were accompanied with loss of embryonic implants and a decrease in fetal and placental weights. The CRP level was significantly decreased and increased at the onset and toward late pregnancy respectively. Oral exposure of pregnant rats to genistein precipitated hypothyroidism, altered some metabolic hormones with a reduction in fetal and placental growth and increased resorption of embryonic implants.